To Be Specific or Not: The Critical Relationship Between Hox And TALE Proteins. Issue 6 (June 2016) - Merabet, Samir; Mann, Richard S.
Abstract : Hox proteins are key regulatory transcription factors that act in different tissues of the embryo to provide specific spatial and temporal coordinates to each cell. These patterning functions often depend on the presence of the TALE-homeodomain class cofactors, which form cooperative DNA-binding complexes with all Hox proteins. How this family of cofactors contributes to the highly diverse and specific functions of Hox proteins in vivo remains an important unsolved question. We review here the most recent advances in understanding the molecular mechanisms underlying Hox–TALE function. In particular, we discuss the role of DNA shape, DNA-binding affinity, and protein–protein interaction flexibility in dictating Hox–TALE specificity. We propose several models to explain how these mechanisms are integrated with each other in the context of the many distinct functions that Hox and TALE factors carry out in vivo . Trends: Hox proteins regulate a wide variety of target genes with different specificity requirements. Hox proteins achieve DNA-binding specificity by binding with TALE family cofactors through a mechanism called latent specificity. The recognition of DNA shape is an independent mechanism of DNA binding site recognition used by Hox–TALE complexes. SELEX-seq and other high-throughput methods are useful approaches for characterizing the DNA binding preferences of DNA binding proteins and complexes of DNA-binding proteins. Highly-specific DNA binding sites tend to be low-affinity, non-consensus sites, whereas high-affinity sites tend to have lower specificity. Hox proteins have a variety of short peptide motifs that are used to interact with TALE cofactors. A variety of TALE cofactors, generated by gene duplication or from the expression of alternative protein isoforms, provide a large number of potential Hox–TALE complexes in vivo, particularly in vertebrates. The paralog-specific regulation of Hox target genes can arise from both DNA-binding- and non-DNA-binding- based mechanisms.